2014
DOI: 10.1051/0004-6361/201423871
|View full text |Cite
|
Sign up to set email alerts
|

Feedback by massive stars and the emergence of superbubbles

Abstract: Context. In a previous paper we investigated the energy transfer of massive stars to the interstellar medium (ISM) as a function of time and the geometrical configuration of three massive stars via 3D-mesh-refining hydrodynamics simulations, following the complete evolution of the massive stars and their supernovae with the exception of non-thermal processes. Aims. To compare our results against observations we derive thermal X-ray properties of the ISM from our simulations and compare them to observations of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 122 publications
5
47
0
Order By: Relevance
“…Similarly, the winds from main sequence stars in three-dimensional superbubble simulations by Krause et al (2014) are significantly stronger than in our models, and the X-ray emission they predict is consequently larger (L X ∼ 3 × 10 33 erg s −1 ). They found that only a few times 10…”
Section: X-ray Emissionsupporting
confidence: 48%
“…Similarly, the winds from main sequence stars in three-dimensional superbubble simulations by Krause et al (2014) are significantly stronger than in our models, and the X-ray emission they predict is consequently larger (L X ∼ 3 × 10 33 erg s −1 ). They found that only a few times 10…”
Section: X-ray Emissionsupporting
confidence: 48%
“…A large interstellar cavity, called Eridanus, extends away from these molecular clouds towards the Sun, and is constrained though X-ray [19] and HI data [20]. Our recent re-analysis of X-ray emission from this region and its comparison with 3D hydrodynamical simulations showed that energy injection and cooling of the superbubble interiors are not in a steady state [21].…”
Section: The Orion Regionmentioning
confidence: 99%
“…The rate at which the gas is converted into stars is controlled locally by the radiation of young stars, turbulence, magnetic fields, and feedback by winds of massive stars and supernovae with the emergence of superbubbles though largescale galactic structures such as the spiral arms and the central bar (e.g., Price and Bate 2009, Elmegreen 2012, Krause et al 2014. The relative role and the links between the processes listed above are still not very clear, but the pressure is an important factor.…”
Section: Star Formation In the Milky Way And Other Galaxiesmentioning
confidence: 99%
“…Evolution and X-ray spectra of three massive star system of 25, 32, and 60 M in a background matrix of 10 cm −3 density was studied by Krause et al (2013Krause et al ( , 2014 in 3D hydrodynamics with an account for optically thin radiative cooling and photo-electric gas heating. They found that the energy injected by supernovae is entirely dissipated in a superbubble on the timescale of about 1 Myr, and that the deposition from the stars to the superbubble did not vary substantially if the massive stars were localized within a distance of < ∼ 30 pc.…”
Section: Hydrodynamical Models Of Massive Star Winds and Superbubblesmentioning
confidence: 99%